A Study of Major Issues and Challenges against Working Women in Society and Workplace: A Sociological Explanation: Examining the Challenges Faced by Working Women in Society and the Workplace (Journal of Advances and Scholarly Researches in Allied Education, 2015)
There are numerous challenges which are faced by working women at a workplace on all the positional levels. The women who are working at ministerial level, they generally face the problem of harsh treatment, extended working hours, less number of leaves/holidays, low wages and insecurity because generally at ministerial level most of the employees are men. At the middle level women faces the challenges in terms of insecurity which is generally related to kind of output required which they are not able to deliver due to diverse commitments towards family and society. At the higher level, women face the challenges related to tasks, accomplishments, greater responsibilities towards the organization and their flexible working hours.